MODERNIZING INDIA’S LEGAL SYSTEM: THE NEED OF ELECTRONIC SYSTEM IN CASE MANAGEMENT AND E-COURTS - Dahiya, Anita; Banerjee, Sulakshana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study aims to demonstrate the Indian Supreme Court’s e-court initiatives to enhance justice. Further ways include the digitalisation of case files, the development of online venues for online dispute resolution, and the facilitation of video conferencing. The goal is to reduce case backlogs, increase accessibility, and promote transparency. However, the technology also creates a digital divide, separating those without access. The judiciary must balance technological investments with closing the digital gap to ensure accessibility and effectiveness. Challenges include missing data and standardisation, as well as poor data quality due to a lack of systematic reviews and capacity building. The e-Courts project has transformed India’s judicial system, improving case management, openness, and security for attorneys and clients. Accessibility and inclusivity must be prioritised when designing and implementing e-court systems. The success of e-Courts depends on addressing technical issues, data breaches, and privacy concerns. A well-defined policy framework, collaboration with experts in data protection, law, and technology, and a strong security system are necessary to address these issues.